Maritime Green Supply Chain Management (MGSCM): An Examination Of Antecedent And Outcome Variables - Jasmi, Muhamad Fairuz Ahmad (2014)
As awareness and consciousness regarding the negative ecological impacts that maritime industry brings to the environment increases, more organizations in maritime around the globe have motivated in establishing sustainable operations including Malaysia’s maritime sectors. Maritime green supply chain management (MGSCM) is a significant movement and interest towards sustainability adoption in many maritime industries around the world and requires major commitment and integration among stakeholders. Similarly, MGSCM has established increasing implementation among service industries especially the Malaysia’s maritime sectors.